-4.9t^2+14t+98=0

Simple and best practice solution for -4.9t^2+14t+98=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4.9t^2+14t+98=0 equation:



-4.9t^2+14t+98=0
a = -4.9; b = 14; c = +98;
Δ = b2-4ac
Δ = 142-4·(-4.9)·98
Δ = 2116.8
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(14)-\sqrt{2116.8}}{2*-4.9}=\frac{-14-\sqrt{2116.8}}{-9.8} $
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(14)+\sqrt{2116.8}}{2*-4.9}=\frac{-14+\sqrt{2116.8}}{-9.8} $

You can always share this solution

See similar equations:

| 0.7t^2+2t-14=0 | | 2y×3=48 | | (5z-1)/3=8* | | 3x2-50x+315=0 | | 6=2a-4 | | 0.25+x/3=x+1/2 | | q/6+8=14 | | 3x=360000 | | 3d+5=2d | | 2x^2+3x=74 | | 9x+1.4=4x+0.0 | | (x-2)(x+5)=(x-3)(x+4)+x2 | | 3x+60=84 | | x2-3x+5=(x+5)2 | | y=-6.1(20)-46.9 | | h(20)=-6.1(20)-46.9 | | 5(-7y+8)+y=-28 | | 6x-9=4x+8 | | 2x-3/4=x+2/3 | | 3+56z? =6 | | 27^4x=9^x+4 | | 27^4x=9^x+$ | | 6(3a+2)=2(4a+11) | | 4(x+1)=2(5x-6) | | 2(3x+7)=4(x+23) | | 8(p-2)=5(p+13) | | 4(g+1)=8(g-8) | | 6(a+2)=2(a+16) | | 4(x+1)=2(x+20) | | 3m+8=-5m-64 | | -k+5=3k-19 | | 5(a+2)-3(a-1)=3 |

Equations solver categories